Studies on Schismatoglottideae (Araceae) of Borneo XXXXVII – Aridarum ashtonii , a new species from the Hose Mountains, and notes on Aridarum burttii - Wong, Sin Yeng; Boyce, P.C (International Aroid Society, Inc., 2015)
Aridarum ashtonii is described as a new species from highland sandstones of the Hose Mountains, Kapit, Sarawak, Malaysian Borneo. Aridarum ashtonii has previously been confounded by the authors with Aridarum burttii, a species occurring on lowland riverine shales. Notes on Aridarum burttii are given and the purported origins of the Type specimen questioned. Aridarum ashtonii and A. burttii are illustrated from living plants, and a key to the five species of the Aridarum Burttii Complex is provided. Recognition of A. ashtonii takes Aridarum to 26 accepted, described species.